Penerapan Pendekatan Ilmiah dalam Kurikulum 2013 pada Mata Pelajaran Akuntansi - Beda, Elias (JOEAI (Journal of Education and Instruction), 2020)
This research aims to find out the application of scientific approach in the 2013 curriculum of accounting subjects to high school students in Ende City. This study uses a type of survey research conducted in four schools. Research sample of 12 accounting teachers. Data is collected by using questionnaires and observations. The results showed (1) accounting teachers were able to design learning plans based on scientific approaches, quantitatively the frequency score of teacher poll results knew 33%, knew 67% and did not know 0%; (2) Observation results show that accounting teachers have not been able to apply a scientific approach to learning well. In conclusion, quantitatively accounting teachers are already aware of the learning plan scientifically, but have not implemented this scientific approach well. The implication is that teachers should get technical training and guidance on scientific approaches so that they can be applied in learning according to scientific procedures. Keywords: Accounting Learning, Scientific Approach, Curriculum 2013